Frequency Analysis of Rainfall Intensities for Bombay (Colaba) - Patel, A.I.; Vanjari, S.S. (Journal of Soil and Water Conservation, 2022)
The hydrologic phenomena which directly influence the interest of an engineer are rainfall, run-off, flood and drought. Rainfall is one of the important hydrologic events. The characteristics of rainfall which are of importance for a redesign engineer are those which are responsible for producing run-off. These characteristics are intensity, duration, frequency of rainfall, time distribution, aerial distribution and geographical distribution. It is rather not possible to predict accurately the future occurrences of these events from given facts and data in a mathematical manner due to complex nature of hydrologic cycle. However, the hydrologic frequency analysis can be used as a tool for predicting the occurrences of future events from the available data, with the help of statistical methods and a sound knowledge of the phenomenon under study.